The impact of regulatory measures on the development of household indebtedness - Jiří Rajl (European Financial and Accounting Journal, 2019)
The purpose of this contribution is to evaluate the regulatory measures of the Czech central bank within the context of financial consumer protection aimed at slowing down the growth of the mortgage market by introducing new recommendations to restrict LTV limits and other indicators. Households are taking advantage of the availability of mortgage loans in an environment of economic growth and low unemployment. However, the growth in real estate prices raises fears of an increase in systemic risk caused by the developing gap between the growth of household indebtedness and the growth in real estate prices. The paper recapitulates the main factors of the growth rate of household indebtedness and the extent to which the adopted recommendations are effective.
Keywords: E44; E58; G21; 650; Credit bureau; Creditworthiness; Financial consumer protection; Household debt; Mortgage loan; Regulation of the credit market